Ugandan optometry students’ experiences of their clinical training: a qualitative study - Mucunguzi, Boaz; Guti, Walker; Tumwine, Moreen; Mubuuke, Aloysius G; Munabi, Ian; Raaheim, Arild; Kiguli, Sarah (BioMed Central Ltd, 2024)
There is a gradual increase in the number of optometry education programs in Africa yet there is limited knowledge on optometry students' experiences of their clinical training. Therefore, the purpose of this study was to explore the optometry students' experiences of their clinical learning environment at a national referral and teaching hospital in Uganda. Between April 2023 and May 2023, face to face in-depth interviews were conducted to explore the experiences of the participants. All 16 optometry students in fourth-year at university were purposefully recruited into the study. Data was collected at the end of the students' clinical training at the eye clinic of a national referral and teaching hospital. Interviews were audio recorded and transcribed for analysis using an inductive thematic approach. Two themes, learning at the eye clinic and organization of the eye clinic, were identified to represent participants' experiences. Each theme had three sub themes. Training optometry students at an eye clinic enhances their clinical skills and knowledge of diagnosing and managing various eye conditions. Future studies should compare optometry students' experiences in lower-level health units to those in national referral hospitals. MEDLINE